Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Từ đầu bài suy ra:
\(\left(x+y\right)+\left(y+z\right)+\left(z+x\right)=\frac{1}{2}+\frac{1}{3}+\frac{1}{4}\)
\(\Leftrightarrow x+y+y+z+z+x=\frac{13}{12}\)
\(\Leftrightarrow2x+2y+2z=\frac{13}{12}\)
\(\Leftrightarrow2\left(x+y+z\right)=\frac{13}{12}\)
\(\Rightarrow x+y+z=\frac{13}{12}:2=\frac{13}{24}\)
\(\Rightarrow x=\frac{13}{24}-\frac{1}{3}=\frac{5}{24}\)
\(y=\frac{13}{24}-\frac{1}{4}=\frac{7}{24}\)
\(z=\frac{13}{24}-\frac{1}{2}=\frac{1}{24}\)
Vậy...
x+y=1/2;y+z=1/3;z+x=1/4
=>2.(x+y+z)=1/2+1/3+1/4=13/12
x+y=1/2=>z=13/12-1/2=7/12
y+z=1/3=>x=13/12-1/3=3/4
z+x=1/4=>y=13/12-1/4=5/6
Ta có :
\(x+y=\frac{1}{2};y+z=\frac{1}{3};z+x=\frac{1}{6}\)
\(\Rightarrow\left(x+y\right)+\left(y+z\right)+\left(z+x\right)=\frac{1}{2}+\frac{1}{3}+\frac{1}{6}\)
\(\Rightarrow2x+2y+2z=\frac{3}{6}+\frac{2}{6}+\frac{1}{6}\)
\(\Rightarrow2\left(x+y+z\right)=1\)
\(\Rightarrow x+y+z=\frac{1}{2}\)
\(\Rightarrow\hept{\begin{cases}\left(x+y+z\right)-\left(x+y\right)=\frac{1}{2}-\frac{1}{2}\Rightarrow z=0\\\left(x+y+z\right)-\left(y+z\right)=\frac{1}{2}-\frac{1}{3}\Rightarrow x=\frac{1}{6}\\\left(x+y+z\right)-\left(z+x\right)=\frac{1}{2}-\frac{1}{6}\Rightarrow y=\frac{1}{3}\end{cases}}\)
Vậy \(x=\frac{1}{6},y=\frac{1}{3};z=0\) .
\(x+y=\frac{1}{2};y+z=\frac{1}{3};z+x=\frac{1}{6}\)
Ta có:\(\left(x+y\right)+\left(y+z\right)+\left(z+x\right)=\frac{1}{2}+\frac{1}{3}+\frac{1}{6}\)
\(\Leftrightarrow2\left(x+y+z\right)=1\)
\(\Leftrightarrow x+y+z=\frac{1}{2}\)
\(\Rightarrow\hept{\begin{cases}\left(x+y+z\right)-\left(x+y\right)=\frac{1}{2}-\frac{1}{2}=0\\\left(x+y+z\right)-\left(y+z\right)=\frac{1}{2}-\frac{1}{3}=\frac{1}{6}\\\left(x+y+z\right)-\left(z+x\right)=\frac{1}{2}-\frac{1}{6}=\frac{1}{3}\end{cases}}\)
Vậy....
vi (x+1)^2>= 0
(y-1)^4>=0
z^2>=0
=>(x+1)^2+(y-1)^4+z^2>=0
Để (x+1)^2+(y-1)^4+z^2=0
=>(x+1)^2=0 =>x+1=0 => x=-1
(y-1)^4=0 =>y-1=0 => y=1
z^2=0 => z=2